PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN KONSUMEN UNTUK MENGGUNAKAN PRODUK KREDIT CEPAT AMAN PADA KANTOR PT. PEGADAIAN DI WILAYAH KOTA MANADO - LASUT, CLIF H (Universitas Sam Ratulangi, 2013)
Based on the observation that the physical appearance and the author do not support facilities in the units of service branch (UPC), the less satisfying service from employees, employee ketidakramahan is a problem that is often found. But disappointments or perceived customer dissatisfaction, will certainly be bad, customers are disappointed and dissatisfied will seek alternative providers of other financial services. In this case the company has to be truly effective and appropriate in applying marketing mix strategy, all aspects of the marketing mix is a chain that cannot be separated and influence each other. Date analysis using a statistical regression and correlation of both simultaneous and partial. Research services marketing mix that consisted of product, price, place, promotion, people, physical appearance and simultaneous processes affect the consumer's decision to significantly to use Fast Secure Credit products (KCA) in unit cabang pegadaian of mining areas of the city of Manado. Services marketing mix that consisted of product, price, place, promotion, people, physical appearance and partial processes affect significantly to consumer decisions using Secure Quick Credit products (KCA) in unit cabang pegadaian of mining areas of the city of Manado. To that for the company to keep the PT Pegadaian continues to maintain and improve the marketing mix strategies, both in terms of product, price, place, promotion, people, process and physical appearance, as influential for consumer decisions Keyword : marketing mix, consumer decision